2022
DOI: 10.1002/jssc.202200185
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐high performance supercritical fluid chromatography‐tandem mass spectrometry method for simultaneous determination of atorvastatin, 2‐hydroxy atorvastatin, and tangeretin in rat plasma and its application to the pharmacokinetic study

Abstract: Recent studies strongly suggest that atorvastatin combination therapy with tangeretin could be beneficial in the treatment of hyperlipidemia. This study aimed to investigate the pharmacokinetic interactions among atorvastatin, its active metabolite 2-hydroxy atorvastatin, and tangeretin after oral administration of atorvastatin with tangeretin in rats. A rapid, selective, and sensitive assay was developed and validated based on ultra-high performance supercritical fluid chromatography-tandem mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Chromatographic conditions were optimized to gain better performance in separation, peak shape and response. The chemistry of stationary phase was one of the most important parameters affecting the retention of the compounds, 22,23 and we found that 3-L could easily get good peak shape and appropriate retention time, but CICT was difficult to elute resulting in long retention time and serious peak tailing, so different chromatographic columns were investigated including Waters XBridge TM C 18 column (75 mm × 4.6 mm, 2.5 μm), ACE Excel 2 C 18 -Amide column (50 mm × 2.1 mm, 2 μm), ZORBAX SB-C 8 (50 mm × 2.1 mm, 3.5 μm) and Kinetex® XB-C 18 (50 mm × 2.1 mm, 2.6 μm). The results showed that only ACE Excel 2 C 18 -Amide column with polar embedded amide as stationary phase met the requirement for excellent separation and acceptable peak shape of CICT.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatographic conditions were optimized to gain better performance in separation, peak shape and response. The chemistry of stationary phase was one of the most important parameters affecting the retention of the compounds, 22,23 and we found that 3-L could easily get good peak shape and appropriate retention time, but CICT was difficult to elute resulting in long retention time and serious peak tailing, so different chromatographic columns were investigated including Waters XBridge TM C 18 column (75 mm × 4.6 mm, 2.5 μm), ACE Excel 2 C 18 -Amide column (50 mm × 2.1 mm, 2 μm), ZORBAX SB-C 8 (50 mm × 2.1 mm, 3.5 μm) and Kinetex® XB-C 18 (50 mm × 2.1 mm, 2.6 μm). The results showed that only ACE Excel 2 C 18 -Amide column with polar embedded amide as stationary phase met the requirement for excellent separation and acceptable peak shape of CICT.…”
Section: Resultsmentioning
confidence: 99%